Examples of divine mockery in the Holy Qur’an, a rhetorical study - الأعرجي, ستار حسين محي (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
This study dealt with one of the rhetorical methods in the Book of God the Wise, which is one of the forms of divine speech. Through studying many Qur’anic verses, we notice that this method is one of the arts of Arabic rhetoric, and one of the methods of discourse that affects the people receiving it. This study dealt with the implications of divine disdain for the world of possibility, in which both existence and nonexistence occur. This world is tainted by imperfection and defects, and in it the absolute, immutable perfection of God alone, which is the necessity of existence, the absolute perfection and beauty devoid of every defect, vanishes. I discussed the causes and motives of belittlement, ridicule, or mockery and its purposes, as well as the types of divine mockery, then explained the importance of this purpose in the Holy Qur’an and Arabic rhetoric, especially among writers. The research monitored the Qur’anic verses as appropriate for researching the most important and prominent disparages of God, including what was disparagement of the Noble Qur’an, in which the infidels and many hypocrites emerged and tried to cast doubt on the Noble Qur’an, challenge its verses, and belittle its importance, as well as disparagement of the Jews and Christians. Then I discussed the sources of belittlement, ridicule, or sarcasm in the Holy Qur’an and how the Holy Qur’an dealt with them, in an educational and moral manner, and its goal is to guide man and lead him back to the right path. The veils of darkness and aberration revealed his insight and heart in a rhetorical style characterized by artistic value and influential significance for the recipient. We will try to monitor fragments of mockery, sarcasm, and sarcasm, considering that they lead to common meanings and a single connotation